COVID-19: update in innovazione, ricerca e sviluppo - Francesco Burrai; Luigi Apuzzo; Valentina Micheluzzi (AboutScience Srl, 2020)
Following the pandemic state, produced by the infection with the new coronavirus SARS-CoV-2, and the consequent state of health emergency, it is considered scientifically important to propose an update on ongoing clinical pharmacological trials, the most advanced international projects in the innovation sector and the most important statistical mathematical approaches to use a model for predictive purposes. In Italy there are several experimental molecules subjected to rigorous RCT studies approved by AIFA. In the Research & Development sector, the CERN in Geneve with the "CERN against COVID-19 project" represents the most advanced innovation, while in predictive statistical techniques, the mathematical model with wavelet approach allows to predict variables such as the persistence of the virus or to calculate the probability of transmission, strategic information for health planning.